Landscape of EGFR mutations in lung adenocarcinoma: a single institute experience with comparison of PANAMutyper testing and targeted next-generation sequencing - Jeonghyo Lee; Yeon Bi Han; Hyun Jung Kwon; Song Kook Lee; Hyojin Kim; Jin-Haeng Chung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Background Activating mutations in the tyrosine kinase domain of epidermal growth factor receptor (EGFR) are predictive biomarkers for response to EGFR-tyrosine kinase inhibitor (TKI) therapy in lung adenocarcinoma (LUAD). Here, we characterized the clinicopathologic features associated with EGFR mutations via peptide nucleic acid clamping-assisted fluorescence melting curve analysis (PANAMutyper) and evaluated the feasibility of targeted deep sequencing for detecting the mutations. Methods We examined EGFR mutations in exons 18 through 21 for 2,088 LUADs from July 2017 to April 2020 using PANAMutyper. Of these, we performed targeted deep sequencing in 73 patients and evaluated EGFR-mutation status and TKI clinical response. Results EGFR mutation was identified in 55.7% of LUADs by PANAMutyper, with mutation rates higher in females (69.3%) and never smokers (67.1%) and highest in the age range of 50 to 59 years (64.9%). For the 73 patients evaluated using both methods, next-generation sequencing (NGS) identified EGFR mutation-positive results in 14 of 61 patients (23.0%) who were EGFR-negative according to PANAMutyper testing. Of the 10 patients reportedly harboring a sensitizing mutation according to NGS, seven received TKI treatment, with all showing partial response or stable disease. In the 12 PANAMutyper-positive cases, NGS identified two additional mutations in exon 18, whereas a discordant negative result was observed in two cases. Conclusions Although PANAMutyper identified high frequencies of EGFR mutations, targeted deep sequencing revealed additional uncommon EGFR mutations. These findings suggested that appropriate use of NGS may benefit LUAD patients with otherwise negative screening test results.